Probabilistic Diagnosis Using a Reformulation of the INTERNIST-1/QMR Knowledge Base - Shwe, M. A.; Middleton, B.; Heckerman, D. E.; Henrion, M.; Horvitz, E. J.; Lehmann, H. P.; Cooper, G. F. (Methods of Information in Medicine, 1991)
In Part I of this two-part series, we report the design of a probabilistic reformulation of the Quick Medical Reference (QMR) diagnostic decision-support tool. We describe a two-level multiply connected belief-network representation of the QMR knowledge base of internal medicine. In the belief-network representation of the QMR knowledge base, we use probabilities derived from the QMR disease profiles, from QMR imports of findings, and from National Center for Health Statistics hospital-discharge statistics.We use a stochastic simulation algorithm for inference on the belief network. This algorithm computes estimates of the posterior marginal probabilities of diseases given a set of findings. In Part II of the series, we compare the performance of QMR to that of our probabilistic system on cases abstracted from continuing medical education materials from Scientific American Medicine. In addition, we analyze empirically several components of the probabilistic model and simulation algorithm.
Keywords: Expert Systems; Computer-aided Diagnosis; Probabilistic Inference; Belief Networks